Pengaruh Penerapan Renang Dasar Menggunakan Swimming Coach berbasis Android dan Motivasi Terhadap Hasil Belajar - Gemaini, Andri; Kiram, Yanuar; Komaini, Anton (Jurnal Sporta Saintika, 2022)
The purpose of this study was to determine the effect of applying basic swimming learning using an android-based swimming coach and training motivation on learning outcomes for beginner swimmers. This research was conducted on students who took swimming courses. The number of samples taken was 30 people who came from students majoring in health and recreation, faculty of sports science. The type of data used in this research is correlation research. The data used are primary and secondary data. The test instrument used to test the instrument in this study is the validity test, reliability test. The hypothesis test used is the F test and t test. Meanwhile, to analyze the data used multiple linear regression (Multi Regression Test). Statistical calculations were carried out using the SPSS 20 computer program. From the results of the study, it can be seen that the application application variable (X1) and exercise motivation (X2) simultaneously have a significant effect on the learning outcome variable (Y). This is based on the results of multiple regression analysis calculations Fcount = 0.974 > Ftable 3.32 with a significant level of p-value = 0.179 > 0.05. The application application variable (X1) partially has a significant effect on learning outcomes (Y), which is indicated by tcount = 1.381>0.161 and the significance of p-value = 0.176> 0.05. While the exercise motivation variable (X2) partially has a significant effect on work performance (Y), which is indicated by tcount = 1.388 > 1.32 and the significance of p-value = 0.391 <0.05.